Identification of Plasma Proteome Signatures Associated With Surgery Using SOMAscan. Issue 4 (April 2021) - Fong, Tamara G.; Chan, Noel Y.; Dillon, Simon T.; Zhou, Wenxiao; Tripp, Bridget; Ngo, Long H.; Otu, Hasan H.; Inouye, Sharon K.; Vasunilashorn, Sarinnapha M.; Cooper, Zara; Xie, Zhongcong; Marcantonio, Edward R.; et al.
Abstract : Objectives: To characterize the proteomic signature of surgery in older adults and association with postoperative outcomes. Summary of Background Data: Circulating plasma proteins can reflect the physiological response to and clinical outcomes after surgery. Methods: Blood plasma from older adults undergoing elective surgery was analyzed for 1305 proteins using SOMAscan. Surgery-associated proteins underwent Ingenuity Pathways Analysis. Selected surgery-associated proteins were independently validated using Luminex or enzyme-linked immunosorbent assay methods. Generalized linear models estimated correlations with postoperative outcomes. Results: Plasma from a subcohort (n = 36) of the Successful Aging after Elective Surgery (SAGES) study was used for SOMAscan. Systems biology analysis of 110 proteins with Benjamini-Hochberg (BH) corrected P value ⩽0.01 and an absolute foldchange (|FC|) ≥1.5 between postoperative day 2 (POD2) and preoperative (PREOP) identified functional pathways with major effects on pro-inflammatory proteins. Chitinase-3-like protein 1 (CHI3L1), C-reactive protein (CRP), and interleukin-6 (IL-6) were independently validated in separate validation cohorts from SAGES (n = 150 for CRP, IL-6; n = 126 for CHI3L1). Foldchange CHI3L1 and IL-6 were associated with increased postoperative complications [relative risk (RR) 1.50, 95% confidence interval (95% CI) 1.21–1.85 and RR 1.63, 95% CI 1.18–2.26, respectively], length of stay (RR 1.35, 95% CI 0.77–1.92 and RR 0.98, 95% CI 0.52–1.45), and risk of discharge to postacute facility (RR 1.15, 95% CI 1.04–1.26 and RR 1.11, 95% CI 1.04–1.18); POD2 and PREOP CRP difference was associated with discharge to postacute facility (RR 1.14, 95% CI 1.04–1.25). Conclusion: SOMAscan can identify novel and clinically relevant surgery-induced protein changes. Ultimately, proteomics may provide insights about pathways by which surgical stress contributes to postoperative outcomes. Abstract : Supplemental Digital Content is available in the text